Equações de diferenças: aplicações no ensino médio - Eller, Elcie Sanches [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The equations of differences have applications in Mathmatics (Fractal geometry, for example), in Economy, in Pharmacology, among other subjects. They are used to modeliny dynamical systems that evolute in discrete time intervals. The equations of differences also are called recurrences and can be resolved through iterations. The main objective of this work is to have a study about equations of differences of 1st and 2nd degreed. The main theoretical results and the resolutions methods are showed. The used of difference operators and anti difference operators to resolve the equations of differencesof 1st order and the displacement operator are highlighted, to resolve the equations of differences of 2nd order, in particular, the constant coefficients. Also a behavior study of the equations of differences solutions is made example of applications in the classroom are presented such as contextualized problem situations like the Sierpinski Triangle, the Hanoi Tower and the Fibonacci Sequence, serving as a basis of technology through the GeoGebra Software, of concrete materials and mathematical modeling

As equações de diferenças têm aplicações na Matemática (Geometria Fractal, por exemplo), na Economia, na Farmacologia, entre outras áreas. Elas são usada para modelar sistemas dinâmicos que evoluem em intervalos de tempo discretos. As equações de diferenças também são chamadas de recorrências e podem ser resolvidas através de interações. O principal objetivo deste trabalho é fazer um estudo sobre as equações de diferenças de 1ª e 2ª ordem. Apresentam-se os principais resultados teóricos bem como os métodos de resolução. Destaca-se o uso dos operadores diferença e antidiferença para resolver equações de diferenças de 1ª ordem e, do operador deslocamento, para resolver equações de diferenças de 2ª ordem, em particular, as de coeficientes constantes. Faz-se também um estudo do comportamento das soluções das equações de diferenças. Apresenta-se como exemplos de aplicações em sala de aula, situações problema contextualizadas, como o Triângulo de Sierpinski, a Torre de Hánoi e a Sequência de Fibonacci, que servem de base para o material didático voltado para o Ensino médio, que propõe atividades que favorecem o uso da tecnologia, através do software GeoGebra, de materiais concretos e da modelagem matemática
Keywords: Matemática - Estudo e ensino; Matemática (Ensino médio); Equações diferenciais - Estudo e ensino; Mathematics Study and teaching